Foot Web Space Transfer for Congenital Syndactyly - Yoko Katsuragi Tomioka, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2020)
Summary:. Syndactyly of the hand is commonly treated using local flaps with skin grafts; however, contractures and/or pigmentation pose a challenge, requiring repeated surgery. Here, we describe a case of a 1-year-old boy who underwent web transplantation for syndactyly. To the best of our knowledge, no “web for web” transplantations have been documented in pediatric literature. Because the patient had an “extra” web space, functional and aesthetic reconstruction was performed with careful preparation. The vascular pattern was assessed using high-resolution ultrasonography. The flap was harvested under a microscope, intravascular stenting was performed for secure anastomosis, and the adequacy of circulation in the flap was verified using the indocyanine green test. Each technique in the procedure used by us contributed to making the microsurgery safer. The present case suggests that “web for web” is a favorable treatment option for some cases, although these would be limited in number.